Acuerdos de convivencia escolar y el comportamiento en niños de la Institución Educativa Inicial N°728 Cabollococha 2024 - Perez Dahua, Melissa (2024)
The objective of this research is to determine the relationship between the level of school coexistence agreements and the behavior of children in the Institution Educative Initial N°728, Caballo Cocha, in the year 2024. This study adopts a quantitative approach and is classified as relational research, with a correlational and transactional design. The study population was made up of all the children of the institution, totaling 118 children between 3 and 5 years old. To collect data, the observation technique was used, and as an instrument, an observation guide. These instruments were subjected to validity and reliability tests before their application. For validation, a group of experts evaluated the instruments. The results obtained using a correlation coefficient of 0.744 and a statistical significance level of 0.05. It is concluded that there is a significant relationship between school coexistence agreements and children's behavior, which led to rejecting the null hypothesis and accepting the research hypothesis.